Fracture behavior of sandwich-structured metal/amorphous alloy/metal composites. (15th January 2016) - Tan, H.F.; Zhang, B.; Yang, Y.K.; Zhu, X.F.; Zhang, G.P.
Abstract: The sandwich-structured ultrafine grained (UFG) Ni/Fe78 B13 Si9 amorphous alloy/UFG Ni composite were prepared through the electrodeposition technique. Tensile testing of the sandwich composites was conducted and fracture behavior of the composites was characterized. The results show that the yield and ultimate tensile strengths decrease gradually, while the ductility of the sandwich composite increases with increasing UFG-Ni layer thickness. The fracture mode of the sandwich-structured composite varies with changing the constraint UFG-Ni layer thickness. The local necking of the UFG-Ni layers plays an important role in fracture mode of the sandwich composites. The coupling effect of the UFG-Ni layer and amorphous layer on mechanical performance of the sandwich composites is discussed. Graphical abstract: Highlights: Sandwich-structured ultrafine-grained Ni/amorphous alloy composites were prepared through electrodeposition technique. Tensile properties of the sandwich composites were examined. Fracture behavior of the amorphous alloy ribbons and sandwich composites was investigated. The coupling effect of the UFG-Ni layer and amorphous layer on mechanical performance of the sandwich composites is analyzed.